Optimalisasi Fungsi Media Sosial Sebagai Sarana Publikasi Home Learning - Ulfah, Yetty Faridatul (JOEAI (Journal of Education and Instruction), 2020)
This study aims to analyze the optimization of social media functions as a means of home learning publications in PAUD Istiqlal Jakarta. This research is a qualitative study with content analysis based on website, data in this research was obtained from the official website of Madrasah Istiqlal Jakarta which is located in www.web.mij.sch.id. Social media data was obtained from Instagram (@kelompokbermainistiqlal, @ra_istiqlal), Facebook and Youtube (Istiqlal Jakarta Play Group, Raudhatul Athfal Istiqlal). The results showed that the management of social media platforms such as Instagram, Facebook and Youtube as a function of publications started from (1) publications of theme submissions every week, (2) publications during the online learning process, (3) publication of reports on the results of learning activities at home from parents, and (4) publications of workshop activities / seminars online. In conclusion, social media flatform becomes an important means utilized by PAUD Istiqlal Jakarta in an effort to convey information and publications about home learning. This is also done in order to maintain communication and improve the quality of distance learning (PJJ) between teachers, students and parents. Keywords: Social Media, Home Learning, PAUD Istiqlal